Equality and Empowerment by Gender and Intersecting Social Differentiation in Agri-food Systems: Setting the Stage - Lecoutere, Els; Kosec, Katrina; Quisumbing, Agnes R.; Elias, M.; Bryan, Elizabeth; Puskur, R. (CGIAR GENDER Impact Platform, 2023)
Achieving gender and social equality in agri-food systems can result in greater food security and better nutrition for all—and transform food systems to be more just, resilient and sustainable. Equitable food systems are essential to achieving SDG 5, whose gender equality goal is intrinsically valuable and whose achievement supports progress across all other SDGs. Current thinking has evolved from focusing on gender gaps to enabling gender-transformative change in agri-food systems, fostering gender and social equality and women’s empowerment. A global snapshot of gender and social equality and of women’s empowerment in agriculture and food systems shows that persistent structural barriers in different domains and at multiple scales are the root causes of gaps by gender and intersecting differentiation. Gender-transformative change in agri-food systems hence necessitates a holistic and inclusive approach to dismantle those barriers. Six working papers for a report on the Status of Rural Women in Agri-food Systems, 10 years after the State of Food and Agriculture 2010–11 (SOFA), developed by the CGIAR GENDER Impact Platform address six key themes important for transformative change by gender and intersecting social differentiation, and for women’s empowerment in agriculture and food systems. They are: a. fostering an enabling environment for equality and empowerment in agri-food systems b. making complementary agricultural resources, technologies, and services more gender responsive c. measuring women’s empowerment in agriculture: innovations and evidence d. beyond crops: toward gender equality in forestry, fisheries, aquaculture and livestock development e. addressing gender inequalities and strengthening women’s agency for climate-resilient and sustainable food systems f. closing gender gaps in productivity to advance gender equality and women’s empowerment